The Welĺ-Ordered Countries - Lane, Jan-Erik (European Journal of Applied Sciences, 2022)
Today there is a set of well-ordered countries to which many people would liķe to move. What is their country advantage? Reply: they are well-ordered in state and society. This key word is better than capitalist democracy or social liberalism or social democracy.